Development of emotional empathy in future educators during the process of professional formation - Maksat Aitzhanov; Ulzharkyn Abdigapbarova; Symbat Bekmuratova; Raissa Izmagambetova; Nazgul Kozhamkulova; Nadezhda Zhiyenbayeva (International Journal of Evaluation and Research in Education (IJERE), 2026)
The aim of this study is to analyze the structural components of empathy among students majoring in pedagogical disciplines and to evaluate the effectiveness of an educational program designed to foster empathy during their professional training. The study involved 120 undergraduate students from two Kazakhstani universities enrolled in creative fields. An experimental approach was adopted in the research. To assess empathy levels, validated questionnaires and psychodiagnostics scales were used. The results of statistical analysis indicated that empathy levels did not significantly change following the completion of the empathy enhancement program. The mean scores across all measurement tools shifted only marginally, and the t-statistics and p-values (p>0.05) pointed to a lack of statistically significant differences. Additionally, analysis of variance (ANOVA) did not reveal any significant differences in the cognitive (F=0.42, p=0.53), emotional (F=0.38, p=0.54), or behavioral (F=0.31, p=0.58) dimensions of empathy. These findings may be attributed to senior students already possessing a relatively high level of empathy, making further development within a short-term program more challenging. The practical significance of the study lies in its in-depth analysis of students’ empathy levels.